Reactions of organoboron compounds enabled by catalyst-promoted metalate shifts. (7th May 2019) - Namirembe, Sheila; Morken, James P.
Abstract : This tutorial review describes recent developments in catalytic reaction design that involve catalyst-promoted 1, 2-metalate shifts as a critical part of the reaction mechanism. Abstract : This tutorial review describes recent developments in catalytic reaction design that involve catalyst-promoted 1, 2-metalate shifts as a critical part of the reaction mechanism. Issues pertaining to catalysis, stereoselectivity, and reaction mechanism are discussed.